Pengaturan Pengaturan Perizinan Penyelenggaraan Pelayanan Kesehatan Berbasis Online Di Indonesia - Ayu, Endang Putri; Budhiartie, Arrie; Fauzani Raharja, Ivan (Mendapo: Journal of Administrative Law, 2022)
The development of increasingly advanced technology has spread to the health sector which is marked by the existence of online-based health services that can be done remotely without having to meet face-to-face. The use of online-based health services has increased due to the Covid-19 pandemic. However, the licensing for the implementation of online-based health services is still unclear, Article 4 paragraph (2) PP No. 47 of 2016 concerning Health Service Facilities states that "in certain cases to fulfill health services and the development of science and technology, the Minister may determine the type of health service facility other than the type of health facility as referred to in paragraph (1)". However, there are no further provisions regarding the licensing of health care facilities that are stipulated in certain circumstances. The purpose of this study is to analyze and identify how the authority to grant licenses for the provision of online-based health services is in Indonesia and how is the form of licensing for online-based health services in Indonesia. This study uses a normative juridical research method by classifying, interpreting and evaluating the legal materials used. The results of this study indicate that (1) the regulation regarding the authority to issue licenses for the provision of online-based health services in Indonesia is still unclear, it is not clear which agency/official is authorized to provide permits for the implementation of online-based health services. (2) the form of licensing for the implementation of online-based health services is a license for its implementation and a license for application services that are facilities for providing online-based health services. Suggestions for the establishment of a policy with the concept of a joint regulation between the Ministry of Health and the Ministry of Communication and Information that regulates the implementation of online-based health services in Indonesia.